Does changing the Functional Movement Screen composite score threshold influence injury risk estimation in junior Australian football players?. Issue 1 (2nd January 2023) - Moore, Emma; Fuller, Joel T.; Milanese, Steve; Jones, Stephen C; Townsley, Alex; Lynagh, Matthew; Chalmers, Samuel
ABSTRACT: This study aimed to identify whether a revised lower Functional Movement Screen (FMS) composite score threshold would be associated with a greater injury risk for junior athletes than the common threshold of≤14. This prospective cohort study included tracking of 809 elite junior male Australian football players for injuries that resulted in a missed game. All athletes completed pre-season FMS testing and a 12-month self-reported retrospective injury questionnaire. Analyses examined the relationship between composite score thresholds of≤14, ≤13, and≤12 and the risk of injury. The relationship between prospective injury and the common composite threshold score of ≤ 14 was dependent on the presence of a recent injury history (relative risk [RR] = 1.45, p = 0.004) in comparison to no recent injury history (RR = 0.98, p = 0.887). Scoring≤12 in the presence of a recent injury history had the greatest diagnostic accuracy but only a trivial increase in injury risk (RR = 1.59, p = 0.001, sensitivity = 0.35, specificity = 0.80, negative and positive likelihood ratios = 0.81 and 1.75). Whilst some small statistical relationships existed between prospective injury and the FMS composite score thresholds, all three thresholds were not associated with a clinically meaningful relationship with prospective injury and were no more effective than retrospective injury for determining athletes at risk of injury.